Whole Cell Biotransformation of 1-dodecanol by Escherichia coli by Soluble Expression of ADH Enzyme from Yarrowia lipolytica - 장지환; 최권영 (Biotechnology and Bioprocess Engineering, 2021)
In this study, alcohol dehydrogenases (ADH) enzymes from Yarrowia lipolytica were investigated for the cloning, soluble expression, and biotransformation of 1-dodecanol to 1-dodecanal, which reaction was thermodynamically unfavorable. Sole expression of ADHs in Escherichia coli did not produce soluble form of cytosolic protein, in spite of the effort to solubilize ADH protein by optimizing IPTG concentration, temperature, and auto-induction medium. Eventually, the active form of soluble ADH proteins was successfully obtained through the co-expression of ADH with chaperone protein in pG-KJE8 vector. After analyzing the individual sets of optimization, it was determined that pET-28a(+)::adh coexpression with the pG-KJE8 molecular chaperone in LB medium with 0.1 mM IPTG, 4 mg/mL arabinose, and 2 ng/mL tetracycline achieved optimum expressions against all of the five ADH proteins. Finally, the whole cell biotransformation activity of ADH2 was determined in 1-dodecanol oxidation to 1-dodecanal, followed by further oxidation to 1-dodecanoic acid.
Keywords: Yarrowia lipolytica; alcohol dehydrogenase; 1-dodecanal; 1-dodecanol; chaperone; whole cell biotransformation